If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2(x + 3) = 6 Reorder the terms: 4 + -2(3 + x) = 6 4 + (3 * -2 + x * -2) = 6 4 + (-6 + -2x) = 6 Combine like terms: 4 + -6 = -2 -2 + -2x = 6 Solving -2 + -2x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -2x = 6 + 2 Combine like terms: -2 + 2 = 0 0 + -2x = 6 + 2 -2x = 6 + 2 Combine like terms: 6 + 2 = 8 -2x = 8 Divide each side by '-2'. x = -4 Simplifying x = -4
| 9xy^4+5x^4y= | | 4.5x-1=75.5 | | 2v+4=6 | | (9y+17)=(11y+17) | | 6(7-8a)=-8(6a+5) | | 40+5w=70+2w | | .46/.27=x | | 3/11=x | | 7/15=x | | 20c=12c+72 | | 3x+bx=z | | 43.4-0.39*78= | | (x+3)y=1 | | 43.4-0.39(.78)= | | 1/3(5/8)=x | | (2x+1)*9+5=23 | | 39.5x+9=4 | | 2-1p-2=-1p+6+6 | | -7(t+8)+2t=3+t | | -1/5(3/7)=x | | 5ln(3x+8)=30 | | 3y^3=12y | | -10=-3p+3+4p | | 2cos(x)=-2cos(2x) | | 4x-10+3x+10=180 | | 8(2x-3)=3x-12 | | 2cos(x)=-2cost(2x) | | ln(7x-4)=8 | | 2+87=7-8 | | 3x-12x+12=60 | | 0.499x-974.6= | | 7-8x=-7-5 |